ANALISIS KEBUTUHAN PROFESIONALISME GURU SEKOLAH DASAR PASCA SERTIFIKASI - Haenilah, Een Y. (Jurnal Sekolah Dasar, 2015)
Abstract: This ex post facto research was intended to find out the independent variables which were related to (a) professional competences (the professional development, the knowledge understanding, the subject mastery); (b) pedagogic competences (the development of the teaching and learning plans, the implementation of the teaching and learning, the assessment); and (c) social competences (the interaction with the students, the other teachers, the parents, and the community). The samples were taken 5% out of 2500 state elementary school teachers who had passed the certification in Bandar Lampung as the population. The results of the study suggested that the mastery of the professional, pedagogic, and social competences had not been fully sought by the teachers yet.Keywords: professionalism, post certification, competences, elementary school teachers.Abstrak: Penelitian ex post facto ini bertujuan untuk mengetahui nilai variabel mandiri, yang berhubungan dengan (a) kompetensi profesional (pengembangan profesi, pemahaman wawasan, penguasaan bahan kajian); (b) kompetensi pedagogik (penyusunan rencana pembelajaran, pelaksanaan pembelajaran, penilaian); dan kompetensi sosial (interaksi dengan peserta didik, sesama guru, orangtua, dan masyarakat sekitar). Sampel diambil 5% dari populasi 2500 guru SDN yang sudah lulus sertifikasi di Kota Bandar Lampung. Hasil penelitian menunjukkan penguasaan kompetensi profesional, pedagogik, dan kompetensi sosial belum sepenuhnya diupayakan oleh para guru.Kata kunci: profesionalisme, pasca sertifikasi, kompetensi, guru SD.